Advances in Nephelometry through the Ecotech Aurora Nephelometer - Steve Chamberlain-Ward; Felicity Sharp (The Scientific World Journal)
The challenge for instrument manufacturers is to continuously improve and evolve their instrumentation to keep pace with scientific research. One field where this is evident is atmospheric aerosol research. The variety in aerosol size, shape, chemical composition, and their ability to change properties under varying atmospheric conditions creates many challenges in quantifying their impact on the global energy balance. As such a wide variety of instrumentation from a selection of manufacturers are used for analysing aerosols, all of which provide a little extra information for deciphering the puzzle. Recent advancements in commercial nephelometers by Australian manufacturer Ecotech have helped to piece some more of this puzzle together. This paper will detail these advances.